Awareness and Knowledge of Physiotherapy among Secondary Students in Kuala Terengganu - Mazni, Kamal; Naresh Bhaskar, Raj; Mohd Haidzir, Manaf (INTI International University, 2023)
Physiotherapy is a healthcare profession concerned with human function and mobility, as well as the maximisation of potential. In recent days, though the awareness about the Physiotherapy profession is increasing, maybe still the complete awareness is not achieved. There is a high percentage of students who hold incorrect beliefs, necessitating the inclusion of specific teaching about it during undergraduate training. The purpose of the study was: (1) to examine the level of awareness regarding physiotherapy among secondary students in Kuala Terengganu, (2) to identify level of knowledge regarding physiotherapy among secondary students in Kuala Terengganu and (3) to determine the relationship between the level of awareness and knowledge regarding physiotherapy among secondary students in Kuala Terengganu. This is a quantitative cross-sectional study and conducted by online survey. The survey instrument for the study was a four sectioned, self-administered questionnaire. Section A was on demographic data (4 questions), while section B was on level of awareness regarding physiotherapy (12 questions). Section C required information on level of knowledge about physiotherapy practise (6 questions) while section D was on physiotherapy as a career (5 questions). A total of 388 of student’s form four and form five from 23 of SMK in Kuala Terengganu participated in the study. The method for sampling applied was convenience sampling. The respond of this study is 100% (n=338). Majority of respondents is form four (n= 205, 60.7%), with age 16 years old (n=205, 60.7%), female gender (n= 208, 61.2%) and Malay race (n=187, 55.3%). The level of awareness of physiotherapy is (n=145, 54.3%) and the level of knowledge of physiotherapy is (n= 65, 24.3%). The relationship between level of awareness and knowledge is (r= 0.189, CI=1.2449, 1.2744, p value= 0.002). The result shown there is a statistically significant, positive and weak correlation between level of awareness and level of knowledge regarding physiotherapy among secondary students (r=0.189, p=0.002).